2013
DOI: 10.1037/a0028140
|View full text |Cite
|
Sign up to set email alerts
|

Correcting injunctive norm misperceptions motivates behavior change: A randomized controlled sun protection intervention.

Abstract: The present research demonstrates the utility of correcting injunctive norm misperceptions for promoting healthy behaviors. That attitudes changed in response to PNF and mediated the norm-intention relationship suggests a method for influencing attitudes that may limit reactance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 58 publications
(60 reference statements)
2
90
2
Order By: Relevance
“…9 Correcting misperceptions of perceived norms has resulted in increased healthy behavior. 8 Increasing HCP awareness that annual influenza vaccination is expected by parents may promote HCP vaccination and facilitate hospitals adopting a policy of required influenza vaccination of HCP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Correcting misperceptions of perceived norms has resulted in increased healthy behavior. 8 Increasing HCP awareness that annual influenza vaccination is expected by parents may promote HCP vaccination and facilitate hospitals adopting a policy of required influenza vaccination of HCP.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive norms refer to the behavior of most people in a certain situation. 8 Injunctive norms refer to whether a behavior is approved by a particular group and are powerful motivators of behavior. 8 In our study, the majority of parents expected HCP to be vaccinated against influenza, suggesting this is an injunctive norm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence has demonstrated that the need to correct misperceptions is essential across a broad range of populations and health behaviours e.g. sun protection (Reid & Aiken, 2013), vaccinations (Nyhan & Reifler, 2015), breastfeeding (Reinsma et al, 2015) and obesity (Duncan et al, 2011). Consequently, identifying misperceptions and rectifying them through modern technology would appear to provide an opportunity to overcome barriers associated with more traditional modes of programme delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that descriptive norms have a direct influence on behavior, whereas injunctive norms have an indirect influence, altering beliefs or cognitions en route to behavior (Cialdini, 2003). Indeed, experiments support that injunctive norms operate through evaluations and attitudes (Cialdini, 2003; Reid & Aiken, 2013). However, to our knowledge, whether descriptive norms also have an indirect effect through evaluations has not been examined.…”
mentioning
confidence: 99%